Carbon Nanolayer‐Coated Na3V2(PO4)3 Nanocrystals Embedded in Conductive Carbon Matrix as High‐Performance Cathode for Sodium‐Ion Batteries. Issue 18 (17th July 2018) - Wan, Xin; Liu, Kelu; Lei, Ping; Zheng, Wenting; Xiang, Xingde; Sun, Molong
Abstract: Na3 V2 (PO4 )3 is a promising cathode material for sodium‐ion batteries. However, the design of appropriate carbon coatings is necessary for improving the Na‐storage performance of this material to overcome the intrinsically low electron conductivity and therefore sluggish reaction kinetics. Herein, carbon nanolayer‐coated Na3 V2 (PO4 )3 nanocrystals embedded in a conductive carbon matrix (NVP/C) are fabricated by using a facile in‐situ synthesis method with controlled utilization of graphene‐oxide nanosheets. Structural and electrochemical properties of the as‐synthesized NVP/C material are analyzed by combining X‐ray diffraction, Fourier‐transform infrared spectroscopy, scanning electron microscope, transition electron microscope, and electrochemical measurements. The optimized NVP/C material exhibits a unique nanostructure consisting of Na3 V2 (PO4 )3 nanocrystals with an average size of ∼60 nm and carbon nanolayers with uniform thickness of ∼5 nm. As electrode, the material delivers a high reversible capacity of 114.8 mAh g −1 at 0.2 C, superior high‐rate capability with a discharge capacity of 101.8 mAh g −1 at 10 C, and excellent cycling performance with capacity retention of 91 % after 1000 cycles. The finding indicates that constructing carbon‐coating nanolayers and a conductive carbon matrix is an important strategy to achieve high‐quality NVP/C material for advanced sodium‐ion batteries. Abstract : That's a wrap : carbon nanolayer‐coated Na3 V2 (PO4 )3 nanocrystals embedded in a conductive carbon matrix are fabricated by using a facile in‐situ synthesis method with controlled utilization of graphene‐oxide nanosheets. As cathode for sodium‐ion batteries, it achieves excellent electrochemical performance with a reversible capacity of 101.8 mAh g −1 at 10 C and a capacity retention of 91 % after 1000 cycles.